Pemanfaatan Media Tiktok dan WhatsAap sebagai Sarana Dakwah di Majelis Taklim Arofah di Dusun Karang Prajegan Sukorejo Ponorogo - Fajar Fadhilah; Miftaku Ni'amah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of community service activities is the use of social media as a means of da'wah, which is to provide information, communicate, and keep records about all Taklim Arofah meetings related to education. In this activity, direct observation was carried out at the Baiturrohman Mosque in the Karang Hamlet area, Prajegan village, Sukorejo District, Ponorogo Regency, and documentation of the taklim meeting was included in the Tiktok media. In addition, the manager and chairman of the Taklim council in Karang Hamlet were interviewed directly to get information about the implementation of service activities. The result of this service is the use of social media platforms such as Tiktok and WhatsApp as a source of information, a place for documentation, and a communication tool for every Taklim council meeting and community activity held at the Baiturrohman Mosque in Karang Hamlet, including supporting photos.